Bilingualism - Mohamed Salleh, Rabiah Tul Adawiyah (2019)
Are you a bilingual/multilingual? Have you ever wondered how you learn to speak all these languages? Are you intrigued to know how humans acquire language (s)? If you answer yes, then join us for a talk on how humans acquire language (s).